Whey proteins: targets of oxidation, or mediators of redox protection - YALÇIN, AHMET SUHA (TAYLOR & FRANCIS LTD, 2019)
Bovine whey proteins are highly valued dairy ingredients. This is primarily due to their amino acid content, digestibility, bioactivities and their processing characteristics. One of the reported bioactivities of whey proteins is antioxidant activity. Numerous dietary intervention trials with humans and animals indicate that consumption of whey products can modulate redox biomarkers to reduce oxidative stress. This bioactivity has in part been assigned to whey peptides using a range of biochemical or cellular assays in vitro. Superimposing whey peptide sequences from gastrointestinal samples, with whey peptides proven to be antioxidant in vitro, allows us to propose peptides from whey likely to exhibit antioxidant activity in the diet. However, whey proteins themselves are targets of oxidation during processing particularly when exposed to high thermal loads and/or extensive processing (e.g. infant formula manufacture). Oxidative damage of whey proteins can be selective with regard to the residues that are modified and are associated with the degree of protein unfolding, with alpha-Lactalbumin more susceptible than beta-Lactoglobulin. Such oxidative damage may have adverse effects on human health. This review summarises how whey proteins can modulate cellular redox pathways and conversely how whey proteins can be oxidised during processing. Given the extensive processing steps that whey proteins are often subjected to, we conclude that oxidation during processing is likely to compromise the positive health attributes associated with whey proteins.
Keywords: Antioxidant; bioavailable; gastrointestinal digestion; glycation; infant formula; oxidative damage; processing; racemised amino acids; whey proteins; GLYCATION END-PRODUCTS; MAILLARD REACTION-PRODUCTS; HUMAN ALPHA-LACTALBUMIN; CACO-2 CELL MONOLAYERS; OXIDIZED AMINO-ACIDS; MILK-PROTEINS; ANTIOXIDANT ACTIVITY; BETA-LACTOGLOBULIN; INFANT-FORMULAS; DIETARY WHEY